Preservice Teachers' Attitudes Toward Inclusion and Toward Students with Special Educational Needs from Different Ethnic Backgrounds. Issue 3 (2nd July 2016) - Markova, Maria; Pit-Ten Cate, Ineke; Krolak-Schwerdt, Sabine; Glock, Sabine
Abstract : Drawing on social cognition frameworks, we experimentally examined preservice teachers' implicit attitudes toward students with special educational needs (SEN) from different ethnic backgrounds and preservice teachers' explicit attitudes toward inclusive education. Preservice teachers ( N = 46) completed an evaluative priming task and questionnaires. Results showed indifferent implicit attitudes toward students with SEN with immigrant backgrounds and positive implicit attitudes toward those without immigrant backgrounds. Furthermore, participants reported a high motivation to act without prejudice toward minorities but held less favorable explicit attitudes toward inclusion of students with SEN, especially students with behavioral problems. Differential patterns of implicit and explicit evaluations could bias teachers' interactions with students. Findings are discussed with respect to implications for educational practice and research.